GR_GERICHTE ZK2 2011 16 vom 27. April 2011 , Berufung OR Werkvertrag/Verlagsvertrag - GR Gerichte (2011)
Löschung gemäss Art. 153 HRegV | Berufung OR Handelsregister/Handelsfirma/kaufmännische Buchführung